2018
DOI: 10.1016/j.ejmg.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of septo-optic dysplasia with focus on prevalence and maternal age – A EUROCAT study

Abstract: Septo-optic nerve dysplasia is a rare congenital anomaly with optic nerve hypoplasia, pituitary hormone deficiencies and midline developmental defects of the brain. The clinical findings are visual impairment, hypopituitarism and developmental delays. The aim of this study was to report prevalence, associated anomalies, maternal age and other epidemiological factors from a large European population based network of congenital anomaly registries (EUROCAT). Data from 29 full member registries for the years 2005-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 22 publications
1
27
0
5
Order By: Relevance
“…Both rare congenital diseases are heterogeneous genetic and clinical disorders. Septo-optic dysplasia in Europe has an incidence of 1.9–2.5 cases per 10,000 births (Garne et al, 2018 ), while the prevalence of holoprosencephaly is 1 case in 10,000 births (Leoncini et al, 2008 ; Kauvar and Muenke, 2010 ; Yi et al, 2019 ; see a systematic review in Orioli and Castilla, 2010 ).…”
Section: Alterations Of Genes Implicated In Hypothalamic Development mentioning
confidence: 99%
“…Both rare congenital diseases are heterogeneous genetic and clinical disorders. Septo-optic dysplasia in Europe has an incidence of 1.9–2.5 cases per 10,000 births (Garne et al, 2018 ), while the prevalence of holoprosencephaly is 1 case in 10,000 births (Leoncini et al, 2008 ; Kauvar and Muenke, 2010 ; Yi et al, 2019 ; see a systematic review in Orioli and Castilla, 2010 ).…”
Section: Alterations Of Genes Implicated In Hypothalamic Development mentioning
confidence: 99%
“…Some registries added the fourth digit code from British Associations extension of ICD-10 for Q043 for further specification (agyria/lissencephaly, microgyria/polygyria, hydranencephaly, reduction anomalies of cerebrum, reduction anomalies of cerebellum). A previous article has reported data from the cases with septo-optic dysplasia,11 which for completeness are also included in this article. Not all registries contributed data for all 10 years.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study of septo-optic dysplasia11 found evidence that some registries were under-reporting cases and developed a method to estimate the prevalence adjusting for this under-reporting. In brief, for each separate anomaly, the average prevalence among the 15 registries with the highest prevalence is calculated using a random-effects meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in retrospective regional study conducted in Canada the annual incidence reached even 53 in 100 000. [124], [125] The etiology of SOD is not fully explained, it is thought that it can be caused by viral infections, environmental teratogens and vascular or degenerative damage. Other factors include parental age, parity, alcohol and substance abuse, smoking, antenatal bleeding or ethnicity.…”
Section: Other Syndromesmentioning
confidence: 99%